2022
DOI: 10.1111/ejn.15527
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of deviance detection in auditory brainstem responses of bats

Abstract: Identifying unexpected acoustic inputs, which allows to react appropriately to new situations, is of major importance for animals. Neural deviance detection describes a change of neural response strength to a stimulus solely caused by the stimulus' probability of occurrence. In the present study, we searched for correlates of deviance detection in auditory brainstem responses obtained in anaesthetised bats (Carollia perspicillata). In an oddball paradigm, we used two pure tone stimuli that represented the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
(68 reference statements)
4
5
0
1
Order By: Relevance
“…This filtering method is different from the usual narrowband filters between 300-2500 Hz that are used in many ABR studies and that will be discussed later. The strong effect of deviance detection in this late part of the response is in line with previous studies that investigated deviance detection in broadband filtered ABRs with pure tones [7,8]. This confirms that this slow, most likely inferior colliculus-generated [9] wave plays a key role in ABR-based deviance detection.…”
Section: Deviance Detection In Broadband Filtered Abrs Differs Betwee...supporting
confidence: 90%
See 3 more Smart Citations
“…This filtering method is different from the usual narrowband filters between 300-2500 Hz that are used in many ABR studies and that will be discussed later. The strong effect of deviance detection in this late part of the response is in line with previous studies that investigated deviance detection in broadband filtered ABRs with pure tones [7,8]. This confirms that this slow, most likely inferior colliculus-generated [9] wave plays a key role in ABR-based deviance detection.…”
Section: Deviance Detection In Broadband Filtered Abrs Differs Betwee...supporting
confidence: 90%
“…Given that wave ii and iii represent neural activity in the cochlear nucleus and superior olivary complex, respectively [14], this finding strongly supports the hypothesis that auditory probability encoding at population level is happening already below the inferior colliculus, as it has been suggested in former studies [8,15]. In fact, effects of novelty detection have recently been described for an even lower auditory structure, the cochlea [16,17].…”
Section: Abrssupporting
confidence: 82%
See 2 more Smart Citations
“…The audiogram of H. pratti showed that their auditory systems responded to a frequency range of 5 to 80 kHz. Therefore, spectrally non-overlapping noise can activate some neurons, and these neurons may synapse on neurons in the frequency range of echolocation signals through local neural circuits, activating an inhibitory neural network ( Seybold et al, 2015 ; López-Jury et al, 2021 ; Wetekam et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%